2022
DOI: 10.3389/fphar.2022.1033026
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of vitamin D supplementation in adults with metabolic syndrome: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background: Studies have shown the association of vitamin D status with the development of metabolic syndrome (MetS), which has attracted an extensive research interest with inconsistent results. Therefore, we hypothesized that vitamin D supplementation (VDS) will benefit adults with MetS.Aims: To test our hypothesis, we performed a meta-analysis to evaluate the effect of VDS on MetS in adults using relevant biomarkers such as anthropometric parameters, blood pressure, blood lipid profile, glycemia, oxidative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 104 publications
0
10
1
2
Order By: Relevance
“…Many studies have shown that low serum 25(OH)D concentration was associated with adverse lipid status (32), and some studies indicated that vitamin D supplementation could improve serum TC, TG, and LDL-C levels also in patients with T2DM (13,14) and in subjects with metabolic syndrome (33). The effect of vitamin D supplementation on TG levels can be mediated through (1) increased calcium levels; (2) suppression of parathyroid hormone (PTH) secretion; (3) inhibition of lipolysis; (4) suppression of inflammation; (5) suppression of renin-angiotensin-aldosterone system (RAAS) activity; (6) its interaction with glucocorticoids and sex hormones; (7) upregulation of adiponectin; (8) improvement in insulin resistance and insulin levels; (9) its direct inhibition of the expression of nuclear factor sterol regulatory element-binding protein 1c (SREBP1c) involved in hepatic TG synthesis; (10) increased TG clearance by upregulation of lipoprotein lipase (LPL), neutral sphingomyelinases, PPARγ, and adipocyte-binding protein 2 (AP2); or by (11) upregulation of mitochondrial oxidation (34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that low serum 25(OH)D concentration was associated with adverse lipid status (32), and some studies indicated that vitamin D supplementation could improve serum TC, TG, and LDL-C levels also in patients with T2DM (13,14) and in subjects with metabolic syndrome (33). The effect of vitamin D supplementation on TG levels can be mediated through (1) increased calcium levels; (2) suppression of parathyroid hormone (PTH) secretion; (3) inhibition of lipolysis; (4) suppression of inflammation; (5) suppression of renin-angiotensin-aldosterone system (RAAS) activity; (6) its interaction with glucocorticoids and sex hormones; (7) upregulation of adiponectin; (8) improvement in insulin resistance and insulin levels; (9) its direct inhibition of the expression of nuclear factor sterol regulatory element-binding protein 1c (SREBP1c) involved in hepatic TG synthesis; (10) increased TG clearance by upregulation of lipoprotein lipase (LPL), neutral sphingomyelinases, PPARγ, and adipocyte-binding protein 2 (AP2); or by (11) upregulation of mitochondrial oxidation (34)(35)(36)(37)(38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis of four studies focusing on the effect of vitamin D supplementation in patients with coronary artery disease, while reporting a significant decrease in serum PTH during the 2-6 month follow-up period, did not reveal any change in serum triglycerides, LDL and HDL-C in vitamin D compared with the placebo group [25]. Additionally, Qi et al recently performed a systematic review and meta-analysis of 13 RCTs with a composite of 1,076 subjects with metabolic syndrome and reported no effects of vitamin D supplementation on either lipid profile or serum PTH levels [26]. Conversely, a systematic review and meta-analysis of 81 RCTs involving roughly 10,000 subjects aged 18-85 years demonstrated that vitamin D supplementation significantly ameliorates lipid profile (triglycerides, LDL-C and HDL-C serum levels) while reducing serum PTH [23].…”
Section: Discussionmentioning
confidence: 98%
“…In the aggregate, some but not all of the evidence from intervention studies is in line with data from ours and other observational studies, as well as the pathophysiology describing the positive actions of vitamin D on glucose and lipids. The treatment of vitamin D deficiency may benefit healthy subjects and some classes of high-risk patients in terms of amelioration of some outcomes associated with glucose and lipid metabolism, while no effects are seen in patients on secondary prevention and in those with metabolic syndrome, in which presumably other mechanisms of lipid metabolism regulation play a prominent role [23][24][25][26]. Inconsistent results across studies may also be evaluated in relation with major differences in the target population and in baseline serum 25(OH)D levels, heterogeneity of follow-up and of vitamin D supplementation, with various consequent effects on serum 25(OH)D levels and on its potential of suppressing serum PTH.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D can also contribute to obesity reduction by two mechanisms: uncoupling the oxidative phosphorylation in adipose cells, thus leading to increased energy consumption, and promoting the mobilization of free fatty acids from fat cells [ 171 ]. On the other hand, there are studies that have shown that in patients with metabolic syndrome, vitamin D did not lower serum lipids and HBA1c and only had lowering effects on blood pressure and insulin resistance [ 172 ]. Due to its renin-angiotensin system inhibition, it can contribute to hypertension control; its contribution to this cardiovascular pathology is also sustained by its role in vasoconstriction and vascular calcification reduction [ 173 ].…”
Section: Potential Role Of Nutrition In Prevention Of Cardiovascular ...mentioning
confidence: 99%